Penguatan Literasi Lingkungan bagi Masyarakat di Desa Tondok Bakaru, Kecamatan Mamasa, Kabupaten Mamasa - Fausan, Muhammad Mifta; Pujiastuti, Indah Panca; Nasir, Yusrianto (Universitas Sulawesi Barat, 2025)
Environmental literacy is a cornerstone in fostering community awareness of the importance of preserving nature. Tondok Bakaru Village faces challenges due to limited environmental literacy among its residents. This community service program aimed to enhance environmental literacy through a comprehensive educational initiative. The implementation method consisted of three stages: planning, program execution, and evaluation. The program was conducted from December 2024 to February 2025, involving 29 participants from the Tondok Bakaru Village community. The material covered includes the concept of environmental literacy, its significance, dimensions of environmental literacy, and strategies for developing environmental literacy within the community. Evaluation results demonstrate significant improvements in three aspects of environmental literacy, with average scores of 70 for environmental knowledge, 74 for environmental attitudes, and 80 for environmental behavior. Participant satisfaction questionnaires yielded an average score above 4.83 on a 5-point scale, indicating the program's success in enhancing understanding and motivating the community to adopt environmentally friendly practices.